HHV‐6–Positive Meningitis in an Immunocompetent Adult: Diagnostic Challenges in Distinguishing Active Infection From Chromosomal Integration: A Case Report - Hatem M. Taha; Anwar Zahran; Orabi Hajjeh; Bara AbuBaha; Mohammed AbuBaha; Omar Marouf (Clinical Case Reports, 2026)
ABSTRACT Consider human herpesvirus 6 (HHV‐6) in immunocompetent adults with viral meningitis when standard tests are negative. Qualitative CSF PCR requires cautious interpretation because it cannot exclude chromosomally integrated HHV‐6. Serial CSF improvement and rapid clinical recovery may support probable self‐limited infection and help avoid unnecessary ganciclovir or foscarnet therapy.